2023
DOI: 10.1093/braincomms/fcad356
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxidative stress in neurodegenerative disorders: a review of reactive oxygen species and prevention by antioxidants

Annwyne Houldsworth

Abstract: Neurological disorders include a variety of conditions, Alzheimer’s disease, Motor Neuron disease, and Parkinson’s disease, affecting longevity and quality of life and their pathogenesis is associated with oxidative stress. Several of the chronic neurodegenerative pathologies of the central nervous system share some common features, such as, oxidative stress, inflammation, synapse dysfunctions, protein misfolding, and defective autophagia. Neuroinflammation can involve the activation of mast cells, contributin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…The KEGG pathway involving intersecting DEGs includes pathway of neurodegeneration-multiple diseases, Alzheimer's disease (AD), diabetic cardiomyopathy, chemical carcinogenesis-reactive oxygen species, HIF-1 signaling pathway, dopaminergic synapse, and central carbon metabolism in cancer (Figure G). The inflammatory hypothesis has been proposed to explain the pathogenesis of neurodegenerative diseases . It has been demonstrated that nicotinamide adenine dinucleotide phosphate (NADPH) oxidase is expressed in activated microglia in the retinas of rd1 mice.…”
Section: Resultsmentioning
confidence: 99%
“…The KEGG pathway involving intersecting DEGs includes pathway of neurodegeneration-multiple diseases, Alzheimer's disease (AD), diabetic cardiomyopathy, chemical carcinogenesis-reactive oxygen species, HIF-1 signaling pathway, dopaminergic synapse, and central carbon metabolism in cancer (Figure G). The inflammatory hypothesis has been proposed to explain the pathogenesis of neurodegenerative diseases . It has been demonstrated that nicotinamide adenine dinucleotide phosphate (NADPH) oxidase is expressed in activated microglia in the retinas of rd1 mice.…”
Section: Resultsmentioning
confidence: 99%
“…These previous studies support our proposition that ergothioneine, which can inhibit excessive ROS production or oxidative stress, may be a way to prevent the development and exacerbation of PD. Furthermore, as oxidative stress is a cause of the onset and exacerbation of various diseases, such as other neurological diseases and diabetes [41,42], it is expected that ergothioneine can be applied as a preventive method for other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…(2) interventions that reduce oxidative stress or other cellular stressors and may indirectly curtail TG2 activity, such as antioxidant agents ethyl pyruvate, N-acetylcysteine (NAC), and α-Lipoic Acid [51,[73][74][75]; and (3) the possible exploration of the genetic modulation of TG2 expression, including gene-silencing techniques and CRISPR/Cas9 gene editing to regulate TG2 levels [76][77][78]. However, the feasibility and safety of the latter approaches need thorough investigation [78].…”
Section: Regulation Of Tg2 Activationmentioning
confidence: 99%